APPLICATION OF CIPM 2007 FORMULA AND ITS INFLUENCE IN DETERMINING UNCERTAINTY DUE TO VARIATION OF AIR DENSITY - Diina Qiyaman Mushoddiqoh; Nur Tjahyo Eka; Toto Sugiharto (Instrumentasi, 2017)
Air density measurement is an important parameter in standard mass calibration. The value is calculated from four measured components : temperature, relative humidity, mole fraction of carbon dioxide, and air pressure of environment where the calibration takes place. Empirical formula to calculate air density is recommended by Comité International des Poids et mesures (CIPM) in 1981/91, then updated in 2007. In this paper, there will be explanation about the differences between CIPM 1981/91 formula and CIPM 2007, their applications to air density calculation and the effects to uncertainty budget, and uncertainty contribution from air density variation to the standard mass calibration. The data is taken from the environment condition in Mass Laboratory of RCM LIPI. From the calculation, the average air density obtained from CIPM 1981/91 formula is 0.0001 kg/m3 smaller than that obtained from CIPM 2007. Air density variation in the mass laboratory is calculated as 0.00572 kg/m3 for CIPM 1981/91 formula and 0.00566 kg/m3 for CIPM 2007. Very small difference makes it insignificant to the uncertainty budget. Uncertainty contribution to standard mass calibration for both formulas are relatively the same, about 0.031 kg/m3, with the sensitivity coefficient 3.0 x 10-06 m3, making it the third largest contributor to the uncertainty budget of mass calibration.